Diplomasi Wolf Warrior Cina dan Relasi Cina-Australia Di Masa Pandemi Covid-19 - Hayati Nufus; Khanisa Khanisa; R. A Rizka Fiani Prabaningtyas (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
The purpose of this study is to analyze China's wolf warrior diplomacy and its implementation on China-Australia relations during the Covid-19 pandemic. Using qualitative method, this study examines wolf warrior diplomacy from the standpoint of public diplomacy concept. In this article, wolf warrior diplomacy is seen as a form of Chinese public diplomacy. This study found that wolf warrior diplomacy aims to shape China's image at the international stage as well as serve domestic public expectations to project China's powerful image. However, the aggressiveness displayed in the wolf warrior diplomacy reflects China's unfavorable image as a threat to other countries. In the context of China-Australia relations, wolf warrior diplomacy has exacerbated existing diplomatic tensions and hinder economic cooperation between the two countries.Keywords: China-Australia, Covid-19, public diplomacy, wolf warrior diplomacy